The wall in the middle of the book - Agee, Jon (New York : Dial Books for Young Readers, 2018)
A knight who feels secure on his side of the wall that divides his book discovers that his side is not as safe as he thought, and the other side is not as threatening.
Booklist starred, September 2018
Pub Weekly, July 2018
Kirkus Starred, August 2018
2.1
K-3
390L
Keywords: Humorous stories; Walls -- Fiction; Toleration -- Fiction; Knights and knighthood -- Fiction; Humorous stories; Humorous fiction